Establishing the Dopamine Dependency of Human Striatal Signals During Reward and Punishment Reversal Learning. (25th November 2012) - van der Schaaf, Marieke E.; van Schouwenburg, Martine R.; Geurts, Dirk E.M.; Schellekens, Arnt F.A.; Buitelaar, Jan K.; Verkes, Robbert Jan; Cools, Roshan
Abstract : Drugs that alter dopamine transmission have opposite effects on reward and punishment learning. These opposite effects have been suggested to depend on dopamine in the striatum. Here, we establish for the first time the neurochemical specificity of such drug effects, during reward and punishment learning in humans, by adopting a coadministration design. Participants ( N = 22) were scanned on 4 occasions using functional magnetic resonance imaging, following intake of placebo, bromocriptine (dopamine-receptor agonist), sulpiride (dopamine-receptor antagonist), or a combination of both drugs. A reversal-learning task was employed, in which both unexpected rewards and punishments signaled reversals. Drug effects were stratified with baseline working memory to take into account individual variations in drug response. Sulpiride induced parallel span-dependent changes on striatal blood oxygen level-dependent (BOLD) signal during unexpected rewards and punishments. These drug effects were found to be partially dopamine-dependent, as they were blocked by coadministration with bromocriptine. In contrast, sulpiride elicited opposite effects on behavioral measures of reward and punishment learning. Moreover, sulpiride-induced increases in striatal BOLD signal during both outcomes were associated with behavioral improvement in reward versus punishment learning. These results provide a strong support for current theories, suggesting that drug effects on reward and punishment learning are mediated via striatal dopamine.